2021
DOI: 10.1089/aid.2020.0305
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir/Cobicistat Is Associated with Negative Outcomes in HIV-Negative Patients with Severe COVID-19 Pneumonia

Abstract: The aim of this study was to evaluate both positive outcomes, including reduction of respiratory support aid and duration of hospital stay, and negative ones, including mortality and a composite of invasive mechanical ventilation or death, in patients with coronavirus disease 2019 (COVID-19) pneumonia treated with or without oral darunavir/cobicistat (DRV/c, 800/150 mg/day) used in different treatment durations. The secondary objective was to evaluate the percentage of patients treated with DRV/c who were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Use of DRV/c in COVID-19 patients has been associated with severe drug-drug interactions with concomitant medications that may contribute to death ( 35 ). Interestingly, we found an increased relative risk for death associated with DRV/c in older patients (more likely taking other drugs), in patients who experienced at hospital highest degree of COVID-19 severity (more likely taking other drugs) and in patients taking hydroxychloroquine, tocilizumab, sarilumab, remdesivir, or corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Use of DRV/c in COVID-19 patients has been associated with severe drug-drug interactions with concomitant medications that may contribute to death ( 35 ). Interestingly, we found an increased relative risk for death associated with DRV/c in older patients (more likely taking other drugs), in patients who experienced at hospital highest degree of COVID-19 severity (more likely taking other drugs) and in patients taking hydroxychloroquine, tocilizumab, sarilumab, remdesivir, or corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical efficacy of a 5-day treatment by the combination Darunavir/cobicistat was assessed and did not show any benefit compared to the standard of care [ 86 ]. Adverse events are controversial according to the studies, one of them showing that it was associated with negative outcomes in HIV-negative patients with severe COVID-19 pneumonia [ 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, only two clinical studies have reported on the effects of DRV/c, and both indicated no significant evidence of improvement with DVR/c [55] (Table 5). In fact, this combination may be dangerous when treating hospitalized COVID-19 patients, as an exploratory retrospective study emphasized its lack of efficacy and highlighted the higher ventilation and mortality rates compared to controls [56].…”
Section: Darunavir/cobicistat (Drv)mentioning
confidence: 99%